A CASE OF MIXED GONADAL DYSGENESIS ACCIDENTALLY DETECTED DURING TREATMENT FOR INGUINAL HERNIA - KITAO, Yoshitaka; NAKAMURA, Ryuichi; MIYAGAKI, Takuya; YASUOKA, Rie; KADOTANI, Yoichi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2004)
Mixed gonadal dysgenesis has a chromosomal aberration mainly due to 45X/46XY chromosomal mosaic, so the lateral gonad may be a testis and the contralateral a linear gonad with Müllerian duct rests including an undifferentiated vagina, uterus, and oviduct. Mixed gonadal dysgenesis is also associated with certain physical features. Although it is principally treated by pediatric physicians and surgeons, we found it accidently in a 45-year-old patient being treated for inguinal hernia. After getting sufficiently informed consent, we successfully removed the linear gonad and Müllerian duct.